2013
DOI: 10.1007/s10930-012-9458-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Y220C Mutation on p53 and Its Rescue Mechanism: A Computer Chemistry Approach

Abstract: Mutation causes inactivation of 'p53' tumor suppressor protein in almost fifty percent of cancers in humans. Outside the DNA-binding surface of p53, Y220C is the most common cancerous mutation. Previous studies have shown that a surface cavity is created by this mutation which destabilizes p53. PhiKan083, a carbazole derivative capable of binding with that cavity, and slows down its thermal denaturation rate. We investigated, theoretically, on mechanisms of structural stability loss due to Y220C mutation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…It has been proposed that the loss of DNA binding function of mutant p53 Y220C is due to the loss of hydrophobic interaction, creating a solvent-accessible cleft at the site of mutation that decreases its thermodynamic stability (69,70). Liu et al have shown that the binding of a small molecule, PK7088, to mutant p53 Y220C in Huh7 cells restored its transcription activity to a level similar to that of wild-type p53 (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the loss of DNA binding function of mutant p53 Y220C is due to the loss of hydrophobic interaction, creating a solvent-accessible cleft at the site of mutation that decreases its thermodynamic stability (69,70). Liu et al have shown that the binding of a small molecule, PK7088, to mutant p53 Y220C in Huh7 cells restored its transcription activity to a level similar to that of wild-type p53 (5).…”
Section: Discussionmentioning
confidence: 99%
“…For Y220C mutation of p53, it is reported that this mutation weakened the anti-tumoral ability of p53 through rapidly denaturing and aggregating p53 (refs. 25,26 ). Whereas, Hep3B cell line is a p53 natural deficiency cell line 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Cys182, Cys229, Cys242 and Cys277 are all exposed on the surface of the core domain, and are potential targets for modifications [64, 81]. According to Lambert et al mut-p53 is more amenable to this type of covalent modification than the wild-type version [80].…”
Section: Agents Restoring P53 Wild-type Conformationmentioning
confidence: 99%